Integration and Impact of GenAI-Coursera in Philosophy-Based French Language Learning on Speaking Skills, Academic Resilience, Critical Thinking Competence, and Self-Evaluation - Umaya, Siti; Hernawan, Asep Herry; Dewi, Laksmi (International Journal of Learning, Teaching and Educational Research, 2026)
The purpose of this study was to investigate the impact of AI-Coursera technology integration in philosophy-based French language learning on critical thinking, self-evaluation, academic resilience, and speaking skills. A quasi-experimental method was used which involved 250 students divided into two groups: an experimental group and a control group. The experimental group received a philosophy-based French language learning intervention with AI-Coursera technology, while the control group received conventional French language learning. Data analysis used MANOVA, t-test, and effect test. The results showed that the integration of GenAI-Coursera in French language learning significantly improved speaking skills, academic resilience, critical thinking skills, and self-evaluation. Improved speaking skills were evident in the use of new language, fluency, and in-depth responses to philosophical questions. Critical thinking skills were enhanced, evident in the use of critical ideas and the reinforcement of French terminology. Academic resilience was enhanced, evident in the ability to resolve conflicts or problems during the learning process. Furthermore, self-evaluation skills were evident in the ability to assess and improve speaking skills. The improvement of all competencies occurs due to GenAI-Coursera's features (discourses, reflective phases, and feedback) and philosophy-based French language teaching principles. Therefore, the use of GenAI-Coursera technology in philosophy-based French language learning not only improves speaking skills but also higher-order thinking skills. This research implies that foreign language teaching requires learning design and the use of GenAI to improve higher-order thinking skills and foreign language competencies. https://doi.org/10.26803/ijlter.25.2.20